Impaired calcium homeostasis is associated with sudden cardiac death and arrhythmias in a genetic equivalent mouse model of the human HRC-Ser96Ala variant - Tzimas, C.; Johnson, D. M.; Santiago, D. J.; Vafiadaki, E.; Arvanitis, DA; Davos, C.H.; Varela, A.; Athanasiadis, N. C.; Dimitriou, C.; Katsimpoulas, M.; Sonntag, S.; Kryzhanovska, M.; et al. (Cardiovasc ResCardiovasc ResCardiovasc Res, 2017)
Aims: The histidine-rich calcium-binding protein (HRC) Ser96Ala variant has previously been identified as a potential biomarker for ventricular arrhythmias and sudden cardiac death in patients with idiopathic dilated cardiomyopathy. Herein, the role of this variant in cardiac pathophysiology is delineated through a novel mouse model, carrying the human mutation in the homologous mouse position. Methods and results: The mouse HRC serine 81, homologous to human HRC serine 96, was mutated to alanine, using knock-in gene targeting. The HRC-Ser81Ala mice presented increased mortality in the absence of structural or histological abnormalities, indicating that early death may be arrhythmia-related. Indeed, under stress-but not baseline-conditions, the HRC-Ser81Ala mice developed ventricular arrhythmias, whilst at the cardiomyocyte level they exhibited increased occurrence of triggered activity. Cardiac contraction was decreased in vivo, ex vivo, and in vitro. Additionally, Ca2+ transients and SR Ca2+ load were both reduced suggesting that cytosolic Ca2+ overload is not the underlying proarrhythmic mechanism. Interestingly, total SR Ca2+ leak was increased in HRC-Ser81Ala cardiomyocytes, without an increase in Ca2+ spark and wave frequency. However, Ca2+ wave propagation was significantly slower and the duration of the associated Na/Ca exchange current was increased. Moreover, action potential duration was also increased. Notably, Ca2+/Calmodulin kinase II (CaMKII) phosphorylation of the ryanodine receptor was increased, whilst KN-93, an inhibitor of CaMKII, reduced the occurrence of arrhythmias. Conclusions: The homologous mutation Ser81Ala in HRC in mice, corresponding to Ser96Ala in humans, is associated with sudden death and depressed cardiac function. Ventricular arrhythmias are related to abnormal Ca2+ cycling across the SR. The data further support a role for CaMKII with the perspective to treat arrhythmias through CaMKII inhibition.
Tzimas, ChristosJohnson, Daniel MSantiago, Demetrio JVafiadaki, ElizabethArvanitis, Demetrios ADavos, Constantinos HVarela, AimiliaAthanasiadis, Nikolaos CDimitriou, ConstantinosKatsimpoulas, MichalisSonntag, StephanKryzhanovska, MariyaShmerling, DoronLehnart, Stephan ESipido, Karin RKranias, Evangelia GSanoudou, DespinaengEngland2017/09/02 06:00Cardiovasc Res. 2017 Sep 1;113(11):1403-1417. doi: 10.1093/cvr/cvx113.
Keywords: Action Potentials/genetics; Animals; Arrhythmias, Cardiac/genetics/*metabolism; Calcium Signaling/drug effects/physiology; Calcium-Binding Proteins/genetics/metabolism; Calcium/*metabolism; Death, Sudden, Cardiac; Disease Models, Animal; Homeostasis/*physiology; Mice, Transgenic; Myocardial Contraction/genetics; Myocytes, Cardiac/metabolism; Ryanodine Receptor Calcium Release Channel/metabolism; Sarcoplasmic Reticulum/drug effects/metabolism